Ceramic wave-absorbing powder and preparation method thereof

By using a combination of ceramic powder, modified carbon nanotubes, and silicon-aluminum composite sol, the aging problem of organic resin adhesives was solved, the mechanical properties and absorption efficiency of the microwave absorbing material were improved, and the durability and safety of the encapsulation structure were enhanced.

CN119275594APending Publication Date: 2025-01-07SUZHOU BOTAO NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411409194.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The use of organic resins as adhesives in existing microwave absorbing materials leads to insufficient long-term reliability and strength, and they are prone to aging, affecting the performance and safety of the encapsulation structure.

Method used

Using ceramic powder as the main component, combined with modified carbon nanotubes, silicon-aluminum composite sol and ceramic hollow microspheres, it is transformed into a ceramic body through high temperature. Silicon-aluminum composite sol is used instead of organic resin as a binder, and the surfaces of the microwave absorbing powder and ceramic hollow microspheres are treated to enhance adhesion and bonding strength.

Benefits of technology

It improves the mechanical properties and strength of the absorbing material, maintains a high surface resistance, broadens the absorbing frequency band, enhances the durability and absorbing efficiency of the packaging structure, and reduces the risk of battery leakage and high temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005077527580000071
    Figure BDA0005077527580000071
  • Figure BDA0005077527580000081
    Figure BDA0005077527580000081
Patent Text Reader

Abstract

The invention relates to the field of wave-absorbing materials, and particularly discloses ceramic wave-absorbing powder as well as a preparation method and application thereof. The invention discloses ceramic wave-absorbing powder as well as a preparation method and application thereof. The ceramic wave-absorbing powder is prepared from the following raw materials in parts by weight: 60-75 parts of ceramic powder, 50-65 parts of wave-absorbing powder, 5-8 parts of silicon-aluminum composite sol and 0.5-1.3 parts of ceramic hollow microspheres, the wave-absorbing powder is prepared from a modified carbon nano tube, Fe-Si-Al and Fe-Si-Cr according to the mass ratio of (2.95 to 3.16) to (1.68 to 2.62) to (3.12 to 3.29); in addition, the preparation method provided by the invention has the advantage of improving the durability of the packaging structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of microwave absorbing materials, and more specifically, to a ceramic microwave absorbing powder and a preparation method thereof. Background Art

[0002] With the development of electronic components, the demand for battery use has increased, and at the same time, higher requirements have been placed on battery safety. The battery packaging structure needs to have properties such as anti-leakage and high temperature resistance to ensure the safety of battery use. Even if the battery is damaged, it can also shield its leakage and high temperature to reduce harm to users and the environment. The packaging structure also needs to have good durability and high surface resistance. After long-term use of the battery, the packaging structure still has good strength and wave absorption performance to ensure the safety of the battery.

[0003] Most of the existing absorbing materials are made by compounding organic resins and absorbing powders to prepare composite materials with absorbing properties. Because they use organic materials as adhesives, they have some shortcomings in long-term reliability and strength. When organic resins are used for a long time, they are prone to aging, and the strength and surface resistance decrease, which affects the use and effect of the packaging structure. Summary of the invention

[0004] In order to improve the durability of the packaging structure, the present application provides a ceramic absorbing powder and a preparation method thereof.

[0005] In the first aspect, the present application provides a ceramic absorbing powder, which adopts the following technical solution: A ceramic absorbing powder comprises the following raw materials in parts by weight: 60-75 parts of ceramic powder, 50-65 parts of absorbing powder, 5-8 parts of silicon-aluminum composite sol and 0.5-1.3 parts of ceramic hollow microspheres; The wave-absorbing powder comprises modified carbon nanotubes, aluminum silicon and chromium silicon in a mass ratio of (2.95-3.16):(1.68-2.62):(3.12-3.29).

[0006] By adopting the above technical scheme, the porcelain powder as the main component of the ceramic absorbing powder can be transformed into a ceramic body at high temperature. The ceramic body has good thermal insulation and insulation properties, and can reduce the battery leakage phenomenon and the danger of high temperature. The silicon-aluminum composite sol is used as an adhesive instead of organic resin. The silicon-aluminum composite sol is used to perform surface treatment on the absorbing powder and the ceramic hollow microspheres, which can enhance the adhesion of the absorbing powder and the ceramic hollow microspheres, so that the bonding force between the porcelain powder, the absorbing powder and the ceramic hollow microspheres is enhanced during the molding process. The absorbing powder and the porcelain powder have stable physical and chemical properties. The finished product has good mechanical properties and strength, is not easy to break, and is conducive to the long-term use of the ceramic absorbing powder. At the same time, the ceramic absorbing powder maintains a high surface resistance, and the absorbing efficiency and absorbing bandwidth of the material are improved.

[0007] Preferably, the preparation method of the modified carbon nanotubes comprises the following steps: adding barium nitrate, ferric nitrate and citric acid into water to form a mixed solution, dispersing the carbon nanotubes in the mixed solution, uniformly dispersing by ultrasonication, dropping ammonia water to adjust the pH to 8.5-9, adding polyethylene glycol and a surfactant, stirring to dissolve, evaporating at a constant temperature in a water bath at 75-80°C to obtain a wet gel, filtering, drying and cooling.

[0008] By adopting the above technical solution, a layer of barium ferrite is attached to the surface of the modified carbon nanotubes. The carbon nanotubes coated with barium ferrite can effectively broaden the absorption bandwidth of the modified carbon nanotubes, so that the absorbing powder has strong absorption peaks in multiple frequency bands, thereby improving the absorbing performance of the absorbing powder.

[0009] Preferably, the molar ratio of the barium nitrate, ferric nitrate and citric acid is (0.9-1.1):(5.8-6.1):(13.9-14.1).

[0010] By adopting the above technical solution and controlling the molar ratio of barium nitrate, ferric nitrate and citric acid, the purity of barium ferrite can be effectively controlled. Citric acid can fully complex with metal ions and reduce the agglomeration between particles, thereby making the obtained barium ferrite particle size smaller, which is conducive to the uniform formation of barium ferrite film on the surface of carbon nanotubes.

[0011] Preferably, the carbon nanotubes are dispersed and pretreated as follows before mixing: the carbon nanotubes are added to a mixture of concentrated sulfuric acid and nitric acid in a volume ratio of 3:1, dispersed evenly by ultrasonication, subjected to hydrothermal reaction at 60-65°C for 4h, cooled naturally, washed, and dried to obtain acidified carbon nanotubes.

[0012] By adopting the above technical solution, the carbon nanotubes treated with the mixed solution can remove amorphous impurities in the carbon nanotubes, and the surface of the acidified carbon nanotubes has polar groups such as hydroxyl and carboxyl, which effectively improves the activity of the carbon nanotubes.

[0013] Preferably, the preparation method of the silica-alumina composite sol comprises the following steps: uniformly mixing aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate, refluxing at high temperature, sealing and standing to cool to room temperature, adding water and an ethanol solution of polyvinyl pyrrolidone, and obtaining the silica-alumina composite sol after magnetic stirring.

[0014] By adopting the above technical scheme, ethyl acetoacetate is used as a chelating agent to chelate aluminum isopropoxide and tetraethyl orthosilicate, thereby effectively improving the stability of the silica-aluminum composite sol, making it less likely to gel or denature when the silica-aluminum composite sol is used for surface treatment of absorbing powders and ceramic hollow microspheres, which is conducive to the stable surface treatment.

[0015] Preferably, the mass ratio of aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate is (5.8-6.2):(2.4-3.1):(0.6-1.1).

[0016] By adopting the above technical scheme, the mass ratio of aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate is controlled, so that the silica-aluminum composite sol has excellent stability and forms a stable sol system. At the same time, the silica-aluminum composite sol has good adhesion and can effectively improve the bonding force between the raw material powders of the ceramic absorbing powder.

[0017] In the second aspect, the present application provides a method for preparing a ceramic absorbing powder, which adopts the following technical scheme: a method for preparing a ceramic absorbing powder, comprising the following steps: diluting a silica-alumina composite sol with water, adding absorbing powder and ceramic hollow microspheres to the diluted silica-alumina composite sol, ultrasonicating for 15 minutes, filtering and drying to obtain a sol-coated powder, ball-milling the sol-coated powder and the porcelain powder to mix evenly, and drying to a moisture content of 3-5% to obtain a ceramic absorbing powder.

[0018] By adopting the above technical scheme, after the silica-aluminum composite sol is diluted with water, the solid content of the sol can be controlled, and the absorbing powder and the ceramic hollow microspheres are added to the diluted silica-aluminum composite sol, so that the surface of the absorbing powder and the ceramic hollow microspheres is coated with a layer of silica-aluminum composite sol. After drying, the silica-aluminum composite sol layer on the surface of the sol-coated powder can improve the surface viscosity of the sol-coated powder, so that the sol-coated powder can be well combined with the ceramic powder. After ball milling and uniform mixing, the bonding force inside the ceramic absorbing powder is improved, and the absorbing material obtained by pressing the ceramic absorbing powder can have excellent mechanical properties and strength.

[0019] Preferably, the diluted silicon-aluminum composite sol has a solid content of 40-50 wt %.

[0020] By adopting the above technical scheme and controlling the solid content of the diluted silica-aluminum composite sol, the surface treatment and coverage of the silica-aluminum composite sol on the absorbing powder and the ceramic hollow microspheres can be effectively controlled, and at the same time, it is beneficial to regulate the thickness and morphology of the silica-aluminum composite sol layer.

[0021] Preferably, the water content of the sol-coated powder is 20-30%.

[0022] By adopting the above technical solution, the moisture content of the sol-coated powder is controlled, and the moisture content and viscosity of the outer layer of silicon-aluminum composite sol can be effectively controlled, thereby improving the bonding between the sol-coated powder and the porcelain powder.

[0023] In summary, this application has the following beneficial effects: 1. Since the present application uses porcelain powder as the main component of ceramic absorbing powder, it can be transformed into a ceramic body at high temperature. The ceramic body has good thermal insulation and insulation properties, which can reduce the danger of battery leakage and high temperature. Silica-aluminum composite sol is used as an adhesive instead of organic resin. Silica-aluminum composite sol is used to perform surface treatment on absorbing powder and ceramic hollow microspheres, which can enhance the adhesion of absorbing powder and ceramic hollow microspheres, so that the bonding force between porcelain powder, absorbing powder and ceramic hollow microspheres is enhanced during the molding process. Both absorbing powder and porcelain powder have stable physical and chemical properties. The finished product has good mechanical properties and strength, is not easy to break, and is conducive to the long-term use of ceramic absorbing powder. At the same time, the ceramic absorbing powder maintains a high surface resistance, thereby improving the absorbing efficiency and absorbing bandwidth of the material.

[0024] 2. In the present application, a layer of barium ferrite is attached to the surface of the modified carbon nanotubes. The barium ferrite-coated carbon nanotubes can effectively broaden the wave absorption bandwidth of the modified carbon nanotubes, so that the wave absorbing powder has a strong wave absorption peak in multiple frequency bands, thereby improving the wave absorption performance of the wave absorbing powder.

[0025] 3. Add absorbing powder and ceramic hollow microspheres into the silicon-aluminum composite sol, so that the surface of the absorbing powder and the ceramic hollow microspheres is coated with a layer of silicon-aluminum composite sol. After drying, the silicon-aluminum composite sol layer on the surface of the sol-coated powder can improve the surface viscosity of the sol-coated powder, so that the sol-coated powder can be well combined with the ceramic powder. After ball milling and uniform mixing, the bonding force inside the ceramic absorbing powder is improved, and the absorbing material obtained by pressing the ceramic absorbing powder can have excellent mechanical properties and strength. DETAILED DESCRIPTION

[0026] The present application is further described in detail below in conjunction with embodiments.

[0027] Preparation Examples 1-6 of Modified Carbon Nanotubes Preparation Example 1 The preparation method of modified carbon nanotubes comprises the following steps: adding barium nitrate, ferric nitrate and citric acid into 100 mL of water to form a mixed solution, wherein the molar ratio of the barium nitrate, ferric nitrate and citric acid is 0.9:5.8:13.9; dispersing 0.4 g of carbon nanotubes in the mixed solution; uniformly dispersing by ultrasonication for 30 minutes; dropping ammonia water to adjust the pH value to 8.5; adding 0.15 g of polyethylene glycol and 0.2 g of hexadecyltrimethylammonium chloride; stirring and dissolving; evaporating at a constant temperature in a water bath at 75°C to obtain a wet gel; and filtering, drying and cooling.

[0028] Preparation Example 2 The preparation method of modified carbon nanotubes comprises the following steps: adding barium nitrate, ferric nitrate and citric acid into 120 mL of water to form a mixed solution, wherein the molar ratio of the barium nitrate, ferric nitrate and citric acid is 1.1:6.1:14.1; dispersing 0.45 g of carbon nanotubes into the mixed solution; uniformly dispersing the mixture by ultrasonic treatment for 40 minutes; dropping ammonia water into the mixed solution to adjust the pH value to 9; adding 0.15 g of polyethylene glycol and 0.2 g of hexadecyltrimethylammonium chloride; stirring and dissolving the mixture; evaporating the mixture at a constant temperature in a water bath at 80°C to obtain a wet gel; and filtering the mixture by suction, drying and cooling the mixture.

[0029] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that in Preparation Example 3, the molar ratio of barium nitrate, ferric nitrate and citric acid is 1.2:4.1:18.2.

[0030] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that in Preparation Example 4, the molar ratio of barium nitrate, ferric nitrate and citric acid is 1:5.9:10.28.

[0031] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, the carbon nanotubes are dispersed and subjected to the following pretreatment before mixing: 1 g of carbon nanotubes are added to 50 mL of a mixture of concentrated sulfuric acid and nitric acid in a volume ratio of 3:1, and after ultrasonic dispersion, they are hydrothermally reacted at 60°C for 4 hours. After natural cooling, they are washed and dried to obtain acidified carbon nanotubes.

[0032] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 1 is that in Preparation Example 6, the carbon nanotubes are dispersed and subjected to the following pretreatment before mixing: 1.2 g of carbon nanotubes are added to 60 mL of a mixture of concentrated sulfuric acid and nitric acid in a volume ratio of 3:1, and after ultrasonic dispersion, the mixture is hydrothermally reacted at 65°C for 4 hours. After natural cooling, the mixture is washed and dried to obtain acidified carbon nanotubes.

[0033] Preparation Examples 7-10 of Silica-Aluminum Composite Sol Preparation Example 7 The preparation method of the silicon-aluminum composite sol comprises the following steps: 40g of aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate are uniformly mixed, wherein the mass ratio of aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate is 5.8:2.4:0.6; after high-temperature reflux, the mixture is sealed and allowed to stand and cool to room temperature; 35mL of water and 5mL of 12wt% polyvinyl pyrrolidone ethanol solution are added; and the silicon-aluminum composite sol is obtained after magnetic stirring.

[0034] Preparation Example 8 The preparation method of the silicon-aluminum composite sol comprises the following steps: 40 g of aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate are uniformly mixed, wherein the mass ratio of aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate is 6.2:3.1:1.1; after high-temperature reflux, the mixture is sealed and allowed to stand and cool to room temperature; 32 mL of water and 5 mL of 10 wt% polyvinyl pyrrolidone ethanol solution are added; and the silicon-aluminum composite sol is obtained after magnetic stirring.

[0035] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 7 is that in Preparation Example 9, the mass ratio of aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate is 5:4:0.8.

[0036] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 7 is that in Preparation Example 10, the mass ratio of aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate is 5.8:1.5:3. Example

[0037] Example 1 A ceramic absorbing powder comprises the following raw materials in parts by weight: 60-75 kg of ceramic powder, 50-65 kg of absorbing powder, 5-8 kg of silicon-aluminum composite sol and 0.5-1.3 kg of ceramic hollow microspheres; wherein the absorbing powder comprises modified carbon nanotubes, iron silicon aluminum and iron silicon chromium in a mass ratio of (2.95-3.16):(1.68-2.62):(3.12-3.29); the ceramic powder is DM95-G750, silicon carbide is purchased from Shanghai Xiangtian Nanomaterial Co., Ltd., silicon nitride is purchased from XT-SIC-01 produced by Wuhu Jikang New Materials Technology Co., Ltd., iron silicon aluminum is purchased from Sichuan Xinjinchun Metal Materials Co., Ltd., iron silicon chromium is purchased from Sichuan Gerun Forest Technology Co., Ltd., ceramic hollow microspheres are purchased from Lingshou County Chengnuo Minerals Co., Ltd., modified carbon nanotubes are selected from the modified carbon nanotubes prepared in Preparation Example 1, and the silicon-aluminum composite sol is selected from the silicon-aluminum composite sol prepared in Preparation Example 7.

[0038] The preparation method of the ceramic absorbing powder comprises the following steps: diluting the silica-aluminum composite sol with water, wherein the solid content of the diluted silica-aluminum composite sol is 40-50wt%, adding absorbing powder and ceramic hollow microspheres to the diluted silica-aluminum composite sol, ultrasonicating for 15 minutes, filtering and drying to obtain sol-coated powder, wherein the water content of the sol-coated powder is 20-30%, ball-milling and mixing the sol-coated powder and the ceramic powder to obtain a ceramic absorbing powder. After drying to a water content of 3-5%, the ceramic absorbing powder is obtained.

[0039] Example 2 A ceramic absorbing powder comprises the following raw materials in parts by weight: 60-75 kg of ceramic powder, 50-65 kg of absorbing powder, 5-8 kg of silicon-aluminum composite sol and 0.5-1.3 kg of ceramic hollow microspheres; wherein the absorbing powder comprises modified carbon nanotubes, iron silicon aluminum and iron silicon chromium in a mass ratio of (2.95-3.16):(1.68-2.62):(3.12-3.29); the ceramic powder is DM95-G750, silicon carbide is purchased from Shanghai Xiangtian Nanomaterial Co., Ltd., silicon nitride is purchased from XT-SIC-01 produced by Wuhu Jikang New Materials Technology Co., Ltd., iron silicon aluminum is purchased from Sichuan Xinjinchun Metal Materials Co., Ltd., iron silicon chromium is purchased from Sichuan Gerun Forest Technology Co., Ltd., ceramic hollow microspheres are purchased from Lingshou County Chengnuo Minerals Co., Ltd., modified carbon nanotubes are selected from modified carbon nanotubes prepared in Preparation Example 2, and silicon-aluminum composite sol is selected from silicon-aluminum composite sol prepared in Preparation Example 8.

[0040] The preparation method of the ceramic absorbing powder comprises the following steps: diluting the silica-aluminum composite sol with water, wherein the solid content of the diluted silica-aluminum composite sol is 40-50wt%, adding absorbing powder and ceramic hollow microspheres to the diluted silica-aluminum composite sol, ultrasonicating for 15 minutes, filtering and drying to obtain sol-coated powder, wherein the water content of the sol-coated powder is 20-30%, ball-milling and mixing the sol-coated powder and the ceramic powder to obtain a ceramic absorbing powder. After drying to a water content of 3-5%, the ceramic absorbing powder is obtained.

[0041] Example 3 The difference between Example 3 and Example 1 is that the modified carbon nanotubes in Example 3 use the modified carbon nanotubes prepared in Preparation Example 3.

[0042] Example 4 The difference between Example 4 and Example 1 is that the modified carbon nanotubes in Example 4 use the modified carbon nanotubes prepared in Preparation Example 4.

[0043] Example 5 The difference between Example 5 and Example 1 is that the modified carbon nanotubes in Example 5 use the modified carbon nanotubes prepared in Preparation Example 5.

[0044] Example 6 The difference between Example 6 and Example 1 is that the modified carbon nanotubes in Example 6 use the modified carbon nanotubes prepared in Preparation Example 5.

[0045] Example 7 The difference between Example 7 and Example 1 is that the silica-alumina composite sol in Example 7 uses the silica-alumina composite sol prepared in Preparation Example 9.

[0046] Example 8 The difference between Example 8 and Example 1 is that the silica-alumina composite sol in Example 8 uses the silica-alumina composite sol prepared in Preparation Example 10.

[0047] Example 9 The difference between Example 9 and Example 1 is that in Example 9, the solid content of the diluted silicon-aluminum composite sol is 20 wt %.

[0048] Example 10 The difference between Example 10 and Example 1 is that in Example 10, the solid content of the diluted silicon-aluminum composite sol is 70 wt %.

[0049] Embodiment 11 The difference between Example 11 and Example 1 is that in Example 11, the moisture content of the sol-coated powder is 10 wt %.

[0050] Example 12 The difference between Example 12 and Example 1 is that in Example 12, the moisture content of the sol-coated powder is 40 wt%.

[0051] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that an equal amount of epoxy resin is used to replace the silica-alumina composite sol and the porcelain powder, and the epoxy resin is bisphenol A liquid epoxy resin BE-188 produced by Jinan Quanxing New Materials Co., Ltd.

[0052] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, no silicon-aluminum composite sol is added, and the ceramic powder, the microwave-absorbing powder and the ceramic hollow microspheres are directly ball-milled and mixed.

[0053] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the absorbing powder in Comparative Example 3 includes modified carbon nanotubes, sendust and chromium iron in a mass ratio of 1.59:3.21:1.58.

[0054] Performance testing According to the raw materials and preparation methods of Examples 1-12 and Comparative Examples 1-3, ceramic absorbing powders were prepared, and the ceramic absorbing powders were pressed into shape to obtain 2 cm×2 cm sheet samples with a thickness of 3 mm. The compressive strength P1 of the samples was tested using a microcomputer compressive strength tester PY-H620-800 carton compression testing machine, and the surface resistivity ρ1 of the samples was tested using an SL030R surface resistance tester. The above results are recorded in Table 1.

[0055] The samples prepared in Examples 1-12 and Comparative Examples 1-3 were subjected to a UV aging performance test: the samples were placed in a UV accelerated aging box of model Q-Lab, the test standard was ISO4892.3, the conditions were UVA-340, 0.76W@340nm, 8h illumination (BPT: 55°C), 4h condensation (BPT: 45°C), and the test time was 144h; then the compressive strength tester and the surface resistance tester were used to test the compressive strength P2 and the surface resistivity ρ2 of the samples again, and the results were recorded in Table 1.

[0056] The reflection loss of the sample was tested at a frequency of 20 MHz using a vector network analyzer, and the results are recorded in Table 1.

[0057] Table 1 Compressive strength and surface resistivity of samples before and after aging According to Table 1, Examples 1-2 and Comparative Examples 1-3, it can be seen that the ceramic absorbing powders prepared in Examples 1-2 have good mechanical strength, high surface resistivity and good absorbing performance, indicating that the ceramic absorbing powders prepared in Examples 1-2 still have good strength and high surface resistivity after a long period of use, which effectively improves the durability of the ceramic absorbing powders. In Examples 1-2, ceramic powder and absorbing powder are used for compounding, and the ceramic hollow microspheres can effectively improve the mechanical strength of the ceramic absorbing powders. The silicon-aluminum composite sol has a good effect on the mechanical properties of the absorbing powders and the ceramic hollow microspheres. The surface treatment of the spheres can form a layer of silicon-aluminum composite sol layer on the surface of the absorbing powder and the ceramic hollow microspheres, thereby effectively improving the surface adhesion of the absorbing powder and the ceramic hollow microspheres, and then improving the adhesion between the raw material powders of the ceramic absorbing powder, thereby improving the internal adhesion and mechanical strength of the sample; both the ceramic powder and the absorbing powder have good chemical and physical stability, and thus have good weather resistance. After long-term use, the performance of the ceramic powder and the absorbing powder is not easy to change, so that the sample after aging treatment still has good mechanical strength and high surface resistance.

[0058] Comparative Example 1 uses epoxy resin instead of silica-aluminum composite sol and porcelain powder. After aging treatment, the sample prepared in Comparative Example 1 has a significantly decreased compressive strength and surface resistance compared with the sample before aging, and the wave absorbing performance is also decreased, indicating that the weather resistance of the organic resin is worse than that of the porcelain powder, which is not conducive to the long-term use of the material. The performance after long-term use has a significant decline, and the safety is reduced.

[0059] In Comparative Example 2, the surface of the absorbing powder and the ceramic hollow microspheres was not treated with the silica-aluminum composite sol. The compressive strength of the samples prepared in Comparative Example 2 decreased before and after aging, indicating that the silica-aluminum composite sol affected the bonding effect between the powders, thereby affecting the compressive strength of the samples. The silica-aluminum composite sol was used to treat the surface of the absorbing powder and the ceramic hollow microspheres to form a silica-aluminum composite sol layer, thereby enhancing the adhesion of the absorbing powder and the ceramic hollow microspheres, thereby improving the bonding strength between the absorbing powder, the ceramic hollow microspheres and the porcelain powder.

[0060] Comparative Example 3 changes the mass ratio of modified carbon nanotubes, sendust and iron silicon chromium in the absorbing powder. The absorbing performance of the samples prepared in Comparative Example 3 decreases before and after aging, indicating that the modified carbon nanotubes, sendust and iron silicon chromium in the absorbing powder have a synergistic effect, which can effectively improve the absorbing performance of the absorbing powder, thereby improving the absorbing performance of the ceramic absorbing powder. When the mass ratio of the three changes, the synergistic effect is weakened, thereby reducing the absorbing performance of the ceramic absorbing powder.

[0061] Compared with Example 1, the wave absorption performance of the sample prepared in Example 3-4 is reduced before and after aging. The molar ratio of barium nitrate, ferric nitrate and citric acid was changed during the preparation of the modified carbon nanotubes used in Example 3-4. The molar ratio of barium nitrate, ferric nitrate and citric acid affected the purity and particle size of the barium ferrite crystals on the surface of the modified carbon nanotubes. The molar ratio of barium nitrate and ferric nitrate affected the formation of barium ferrite crystals. The amount of citric acid added affected the particle size of the barium ferrite. Too much or too little citric acid can easily cause the barium ferrite to agglomerate or have too large a particle size, thereby affecting the uniform formation of the barium ferrite film.

[0062] Compared with Example 1, the wave absorption performance of the samples prepared in Example 5-6 is improved before and after aging. When the modified carbon nanotubes used in Example 5-6 are prepared, the carbon nanotubes are first subjected to acid treatment before modification. After the acid treatment, the amorphous impurities in the carbon nanotubes can be processed, and at the same time, the surface of the acidified carbon nanotubes contains polar groups such as hydroxyl and carboxyl, which effectively improves the activity of the carbon nanotubes and is beneficial to the deposition of barium ferrite on the surface of the carbon nanotubes and the formation of a thin film.

[0063] Compared with Example 1, the compressive strength of the samples prepared in Example 7-8 decreased before and after aging. During the preparation of the silica-aluminum composite sol used in Example 7-8, the mass ratio of aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate was changed. The mass ratio of aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate directly affected the structure of the silica-aluminum composite sol. Ethyl acetoacetate, as a chelating agent, can chelate aluminum isopropoxide and tetraethyl orthosilicate, thereby effectively improving the stability of the silica-aluminum composite sol, so that the silica-aluminum composite sol can uniformly and stably coat the absorbing powder and ceramic hollow microspheres in the subsequent surface treatment, thereby improving the surface viscosity of the absorbing powder and the ceramic hollow microspheres, and then improving the bonding force and mechanical strength of the ceramic absorbing powder.

[0064] Compared with Example 1, the compressive strength of the samples prepared in Examples 9-10 decreased before and after aging. In Examples 9-10, the solid content of the silica-aluminum composite sol when used was changed. The solid content of the silica-aluminum composite sol when used affected the thickness and morphology of the silica-aluminum composite sol formed on the surface of the absorbing powder and the ceramic hollow microspheres. If the solid content is too little, the silica-aluminum composite sol layer on the surface of the sol-coated powder may be thin or incompletely coated, thereby affecting the adhesion of the sol-coated powder. If the solid content is too much, the silica-aluminum composite sol layer on the surface of the sol-coated powder may be thicker or uneven, thereby affecting the adhesion of the sol-coated powder and further affecting the compressive strength of the sample.

[0065] Compared with Example 1, the compressive strength of the samples prepared in Example 11-12 decreased before and after aging. The moisture content of the sol-coated powder was changed in Example 11-12. The moisture content of the sol-coated powder directly affected the moisture content of the silica-aluminum composite sol layer outside the sol-coated powder. The moisture content of the silica-aluminum composite sol layer affected its viscosity. When the moisture content was too low, the adhesion of the sol-coated powder was reduced, which easily reduced the adhesion of the ceramic absorbing powder. When the moisture content was too high, the adhesion of the sol-coated powder was too high, and the sol-coated powder was not easy to mix evenly with the ceramic powder, which made the components of the prepared sample uneven, thereby affecting the mechanical strength of the sample.

[0066] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A ceramic microwave absorbing powder, characterized in that: The method comprises the following raw materials in parts by weight: 60-75 parts of porcelain powder, 50-65 parts of wave-absorbing powder, 5-8 parts of silicon-aluminum composite sol and 0.5-1.3 parts of ceramic hollow microspheres; The wave-absorbing powder comprises modified carbon nanotubes, aluminum silicon and chromium silicon in a mass ratio of (2.95-3.16):(1.68-2.62):(3.12-3.29).

2. The ceramic microwave absorbing powder according to claim 1, characterized in that: The preparation method of the modified carbon nanotubes comprises the following steps: adding barium nitrate, ferric nitrate and citric acid into water to form a mixed solution, dispersing the carbon nanotubes in the mixed solution, uniformly dispersing by ultrasonication, dropping ammonia water into the mixed solution to adjust the pH value to 8.5-9, adding polyethylene glycol and a surfactant, stirring and dissolving, evaporating at a constant temperature in a water bath at 75-80°C to obtain a wet gel, and filtering, drying and cooling.

3. The ceramic microwave absorbing powder according to claim 2, characterized in that: The molar ratio of the barium nitrate, ferric nitrate and citric acid is (0.9-1.1):(5.8-6.1):(13.9-14.1).

4. The ceramic microwave absorbing powder according to claim 2, characterized in that: The carbon nanotubes are dispersed and mixed before being pretreated as follows: the carbon nanotubes are added into a mixture of concentrated sulfuric acid and nitric acid in a volume ratio of 3:1, dispersed uniformly by ultrasonication, and then hydrothermally reacted at 60-65° C. for 4 hours. After natural cooling, the carbon nanotubes are washed and dried to obtain acidified carbon nanotubes.

5. The ceramic microwave absorbing powder according to claim 1, characterized in that: The preparation method of the silicon-aluminum composite sol comprises the following steps: uniformly mixing aluminum isopropoxide, ethyl orthosilicate and ethyl acetoacetate, sealing and cooling to room temperature after high-temperature reflux, adding water and ethanol solution of polyvinyl pyrrolidone, and preparing the silicon-aluminum composite sol after magnetic stirring.

6. The ceramic microwave absorbing powder according to claim 5, characterized in that: The mass ratio of the aluminum isopropoxide, tetraethyl orthosilicate and ethyl acetoacetate is (5.8-6.2):(2.4-3.1):(0.6-1.1).

7. A method for preparing a ceramic microwave absorbing powder according to any one of claims 1 to 6, characterized in that: The following steps are involved: The silica-alumina composite sol is diluted with water, and the absorbing powder and ceramic hollow microspheres are added to the diluted silica-alumina composite sol. After ultrasonic treatment for 15 minutes, the sol-coated powder is filtered and dried to obtain the sol-coated powder. The sol-coated powder and the ceramic powder are ball-milled and mixed evenly. After drying to a moisture content of 3-5%, the ceramic absorbing powder is obtained.

8. The method for preparing a ceramic microwave absorbing powder according to claim 7, characterized in that: The diluted silicon-aluminum composite sol has a solid content of 40-50wt%.

9. The ceramic microwave absorbing powder according to claim 7, characterized in that: The water content of the sol-coated powder is 20-30%.